Analysis of Frequency Types of Pre-analytic Stage Errors in Routine Hematology Examinations in Hospitals - Sela, Meilisa Dwi; Bastian; Aristoteles (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2025)
The pre-analytical stage is one of the most complex stages to control. The pre-analytical stage has a series of variables and several critical points associated with various errors. Pre-analytical stage errors can account for up to 70% of total laboratory errors. The impact of errors at this stage cannot be ignored because the information provided from clinical laboratory results can be influential in up to 60-70% of clinical decisions. This research aims to find out the percentage of results from the analysis of the frequency of errors in the pre-analytic stage in routine hematology examinations in hospitals. This study uses the descriptive-quantitative method with data collection techniques using primary data on laboratory workers at Bhayangkara Hospital Palembang and Muhammadiyah Hospital Palembang, each with 15 respondents. Results, type-stage error pre-analytical examination hematology routine in the laboratory of Hospital "X" received a score 97.3% with a very good category, while in the hospital laboratory "Y"got a score 93.6% with a very good category. Data processing uses univariate analysis, resulting in the finding that there is no significant difference between both hospitals. Conclusion, type stage error pre-analytic inspection routine hematology for staff in the laboratories of Hospital "X and Hospital "Y" Palembang can be stated as good, and there is no significant difference between both hospitals.